Epidemiological profile between 2020 and 2021 of patients with lichen planus treated in a tertiary hospital - Fernanda Del Rio; Thayane Lemos; Felipe Tavares-Rodrigues; Manuela Cabral; Ana L. Sampaio (Sociedade Portuguesa de Dermatologia e Venereologia, 2023)
Background: Lichen planus (LP) is a chronic inflammatory dermatosis of unknown etiology that manifests in various clinical forms on the skin, oral and genital mucosa, scalp, and nails. Reports have suggested that anxiety, stress, diabetes, autoimmune diseases, drugs and genetic predisposition may be triggers of the disease. Meanwhile, the association of LP with hepatitis C virus infection remains controversial. Objectives: To analyze the epidemiological profile of patients treated in a tertiary hospital and compare our findings with those in the literature. Methods: We conducted a retrospective cross-sectional observational study of patients with lesions of histopathologically confirmed LP who were treated in a tertiary hospital from January 2020 to January 2021. Additionally, we analyzed the association of LP with comorbidities, including hepatitis C and smoking. Results: Overall, 24 patients were included in the study. Of these, 19 (79%) were women, and 13 (55%) had comorbidities, including hypertension and diabetes mellitus. Additionally, 29% of the patients were smokers. The most common forms of LP found were cutaneous (15 patients, 63%), followed by a cutaneous plus nail (four patients, 17%), cutaneous plus oral (three patients, 12%) and nail (two patients, 8%) forms. Moreover, 20/24 (83%) patients with documented serology for hepatitis C showed negative results; however, one of these patients was treated for HCV 5 years before the onset of LP. Conclusions: The present study demonstrated that LP is more prevalent in women and those with higher phototypes (Fitzpatrick > III). In addition, it has several associated comorbidities. Meanwhile, although the association of LP with hepatitis C has been reported, we did not observe this in our study. Future studies with larger sample sizes should be conducted to confirm our results.